Carbon fiber–reinforced polymer rod panels for strengthening concrete bridges. Issue 4 (March 2018) - Peiris, Abheetha; Harik, Issam
The practice of using fiber-reinforced polymer laminates and fabric to repair and strengthen concrete structures is well established. What limits the application of fiber-reinforced polymer materials, especially in flexural strengthening, is the equipment and man power needed for continuous application when retrofits take place over waterways or multilane roadways. A carbon fiber–reinforced polymer rod panel system consisting of 1220-mm (48-in) panels made continuous through a finger joint/splice was developed to overcome these limitations. The system's performance hinges on whether forces can be transferred from one panel to another. This study investigated the bond characteristics of carbon fiber–reinforced polymer rods, as well as the flexural behavior of concrete members strengthened with carbon fiber–reinforced polymer rod panels, to improve knowledge of the finger joint's behavior. Bond tests were conducted using double-lap shear specimens on individual rods with both steel and concrete substrates. Further bond tests were performed on small carbon fiber–reinforced polymer rod panels on steel substrate. Flexural tests were carried out under four-point bending on small-scale reinforced concrete beams that were strengthened using continuous carbon fiber–reinforced polymer rod panels and carbon fiber–reinforced polymer rod panels spliced using a finger joint. Case studies of four field applications are presented to provide a better understanding of the system. The new carbon fiber–reinforced polymer rod panels effectively reduce labor and equipment costs for work conducted on bridges with limited access, as they enabled the performance of repair/retrofit operations by a small crew working out of a single work platform.